2017
DOI: 10.14304/surya.jpr.v5n1.2
|View full text |Cite
|
Sign up to set email alerts
|

Pleotropic Acute and Chronic Effects of Leptin to Reverse Type 1 Diabetes

Abstract: Recent studies have demonstrated that leptin can prolong life chronically in rats with poorlycontrolled type 1 diabetes (T1D). Multiple explanations have been proposed to explain leptin's chronic antihyperglycemic effect, including suppression of glucagon release and/or signaling, reductions in hyperphagia and ectopic lipid content, and improvements in insulin sensitivity; it is leptin's ability to reduce plasma glucose relies on all of these effects. In addition, leptin reverses hyperglycemia and diabetic ket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Although the adipokines are synthesized and secreted by the adipose tissue, the expression of adipokines and components of their signaling cascades is shown in the testes (Gurusubramanian & Roy, 2014; Rak, Mellouk, Froment, & Dupont, 2017). The plasma levels of adipokines change dramatically not only in DM2, as a result of obesity and impaired energy metabolism, but also in DM1 due to acute hyperglycemia, reduced insulin signaling and the activation of inflammation and oxidative stress (Perry, 2017; Yazıcı et al, 2012). We have also shown that the expression of visfatin was decreased in the testis of rats with alloxan‐induced DM1 (Gurusubramanian & Roy, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although the adipokines are synthesized and secreted by the adipose tissue, the expression of adipokines and components of their signaling cascades is shown in the testes (Gurusubramanian & Roy, 2014; Rak, Mellouk, Froment, & Dupont, 2017). The plasma levels of adipokines change dramatically not only in DM2, as a result of obesity and impaired energy metabolism, but also in DM1 due to acute hyperglycemia, reduced insulin signaling and the activation of inflammation and oxidative stress (Perry, 2017; Yazıcı et al, 2012). We have also shown that the expression of visfatin was decreased in the testis of rats with alloxan‐induced DM1 (Gurusubramanian & Roy, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Dr. Perry defends these findings in the face of a recent article showing no effect of HPA axis regulation on leptin's glucose-lowering activities. She convincingly argues that the lower insulin levels and presence of sucrose water masked the activities of leptin on the hypothalamus in the contrasting study (Perry 2017). The implications of Dr. Perry's studies are profound.…”
Section: Journal Of Postdoctoral Research January 2017mentioning
confidence: 99%